2015
DOI: 10.1039/c5ra14664j
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of nucleobases on 2D transition-metal dichalcogenides and graphene sheet: a first principles density functional theory study

Abstract: Adsorption characteristics of DNA/RNA nucleobases on monolayers of transition-metal dichalcogenide (TMD) such as molybdenum disulfide (MoS 2 ) and tungsten disulfide (WS 2 ) have been studied using first principles density functional theory (DFT) with vdW-DF method. The same calculations have been performed with PBE and DFT-D2 method for comparison. In addition, a comparative study has been done for adsorption with graphene (GRA) also to compare with MoS 2 and WS 2 . We have found that all nucleobases are phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
73
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(84 citation statements)
references
References 64 publications
(136 reference statements)
9
73
1
1
Order By: Relevance
“…The obtained binding energy and the optimum height with respect to monolayer have been tabulated in table 1. The optimum height is defined as the vertical distance between the center of mass of the molecule and the top S-layer of the 35 . The magnitude of the calculated binding energy exhibits the following order: guanine > adenine/cytosine > thymine for both GGA-PBE and Vdw-DF1 functionals.…”
Section: Resultsmentioning
confidence: 99%
“…The obtained binding energy and the optimum height with respect to monolayer have been tabulated in table 1. The optimum height is defined as the vertical distance between the center of mass of the molecule and the top S-layer of the 35 . The magnitude of the calculated binding energy exhibits the following order: guanine > adenine/cytosine > thymine for both GGA-PBE and Vdw-DF1 functionals.…”
Section: Resultsmentioning
confidence: 99%
“…Using first principle density function theory (DFT), Vovusha and Sanyal indicated that all the four nucleobases interact with MoS2 and WS2 via vdW force, which is consistent with our conclusion. 35 They predicted that for individual nucleobases, the affinity on MoS2 and WS2 follows the order of G > A > T > C with atomic level details. For example, the H atom of the CH3 group in adenine interacts with the S atom of the surface.…”
Section: Dna Desorptionmentioning
confidence: 99%
“…34,35 A comparison was made for DNA adsorption on these materials using fluorescently labeled magnetic nanoparticle probes. 36 MoS2, WS2 and GO can all adsorb single-stranded (ss) DNA while repel double-stranded (ds) DNA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The maximum binding energies obtained by DFT with inclusion of van der Waals interactions for thymine and uracil on graphene are 55.0 and 49.68 kJ mol −1 , respectively. Vovusha and Sanyal also reported that all nucleobases are physisorbed on graphene, MoS 2 and WS 2 sheets . The calculated binding energies of thymine (uracil) adsorbed on graphene, MoS 2 and WS 2 are 70.55 (63.52), 67.62 (58.88) and 67.54 (58.01) kJ mol −1 , respectively.…”
Section: Introductionmentioning
confidence: 89%